(3JaSjQ GdbQBfs - (3efUhQ Hf eMeO Hf YHO GdLHGQ GdSeYGfj GdTGaYj, CHh efUhQ , LeGd GdOjf J (B562 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf hGdYGbHI ddeJbjf hGdUdGI Ydi QShdg eMeO hBdg CLeYjf Gdbhd ai JaSjQ aGJMI GdcJGH s
(3BNQgG (B:s
(3Je GdLRA GdChd ef JaSjQ GdSeYGfi s
(3JTJed Ydi agQS HYOO GdShQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdGHOGd (B- ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B449s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3JaSjQ (B136) s
Keywords: (3GdJaSjQ hYdhe GdbQBfs